Langkah “Merah” Pemikiran Pendidikan Tan Malaka, 1919-1921 - Satriono Priyo Utomo (Department of History, Faculty of Humanities, Diponegoro University, 2020)
The historiography of Tan Malaka, which has been frequently found, discusses his personality as a revolutionary figure, living from one prison to another. The consistency of Tan Malaka in struggling for the absolute independence has been studied for years by the Dutch historian, Harry Poeze. Departing from historiography about Tan Malaka in which have written by Harry Poeze, this study uses the historical method. It discusses Tan Malaka's thoughts on education which originated from his publication in 1921 entitled Sarekat Islam and Onderwijs. Where it can be seen that Tan Malaka puts education as a political tool, in which it has the goal of shaping Indonesian people not only to be intelligent but also to refine their feelings. He rejected the rote learning method that make people become foolish and mechanical-type like machines. Tan Malaka's figure as a political actor has been scrutinized and written comprehensively by using historical source which become adequate. However, there are still very few studies that discuss Tan Malaka's thought. In the activities of practical politics, Tan Malaka was a productive revolutionary figure eflecting his thoughts in a number of works. Not many of the published works have examined Tan Malaka's thoughts about his views on education. Tan Malaka is a movement figure who chose studies in the field of pedagogy (education).